The crystal ball : a Rebecca mystery - Greene, Jacqueline Dembar (American Girl Pub., 2012)
When Rebecca helps her injured neighbor, Mr. Rossi, by caring for his pigeons, she discovers a strange black pigeon with an eerie message warning Mr. Rossi of danger, and consults a fortune teller to learn if she is in danger, as well.